ANALYSIS OF FACTORS, ACTOR READINESS, AND STAKEHOLDER READINESS IN THE ADOPTION OF BLOCKCHAIN FOR MANGOSTEEN SUPPLY CHAIN TRACEABILITY (Jurnal Teknologi Industri Pertanian, 2026)
Blockchain is currently a popular technology for ensuring data security and has the potential to be used across various sectors, especially in the supply chain. Traceability of information is an essential characteristic of blockchain in agricultural commodity supply chains, such as the mangosteen export supply chain, which faces challenges of a long distribution chain and a lack of digitization in the supply chain process, making traceability critical. This study aims to identify supporting and inhibiting factors and to assess the readiness of actors and stakeholders to adopt blockchain technology. Respondents were selected using purposive sampling, involving 19 key actors and stakeholders. Data were collected and analyzed using the TRI method to measure the level of readiness to adopt blockchain technology. The study's results show that the main obstacles identified include concerns about implementation and changes in work culture resulting from limited resources, regulations, and high implementation costs. Meanwhile, the main supporting factors are actors' awareness of the importance of digitization, the potential for transparent and efficient recording, and the ease of tracking. The level of readiness to adopt blockchain among mangosteen supply chain actors is moderate, with an average TRI score of 3.44. This category indicates that supply chain actors are beginning to adopt blockchain technology, but there are still obstacles to be addressed.Keywords:  blockchain adoption readiness, horticultural supply chain,  Technology Readiness Index (TRI)